Clinician perspectives on virtual reality use in physical therapy practice in the United States - Danielle T. Felsberg; Jared T. McGuirt; Scott E. Ross; Louisa D. Raisbeck; Charlend K. Howard; Christopher K. Rhea (PLoS ONE, 2025)
The primary goal of physical rehabilitation is to assess movement impairments and restore function to improve overall quality of life. Virtual reality (VR) may provide the optimal environment to promote these goals due to its motivating and modifiable nature which can be difficult to accomplish through traditional real-world therapeutic methods. Current research of VR for rehabilitation has demonstrated that VR interventions can produce clinically meaningful change in motor outcomes. Despite this, adoption and usage of VR by physical therapy professionals is unclear due to the limited research in this area. Thus, the purpose of this study was to identify the current usage and perspectives of VR in physical rehabilitation among physical therapy professionals. Physical Therapists (PTs) and Physical Therapist Assistants (PTAs) in the United States were recruited to participate in this survey-based study. A total of N = 658 participants completed the survey, which consisted of demographic information followed by the Assessing Determinants Of Prospective Take-up of Virtual Reality (ADOPT-VR2) survey that assesses 12 constructs (e.g., Attitudes, Perceived Usefulness, Facilitating Conditions and Barriers) related to the use of VR in clinical settings. Most respondents reported not using VR in clinical practice (n = 611; 92.9%). For all respondents, the constructs of Attitudes, Perceived Ease of Use, Compatibility, Client Influence, and Self-Efficacy were found to statistically contribute to the prediction of Behavioral Intention to use VR (p < .05). However, for those clinicians using VR in their clinical practice, Superior Influence and Perceived Behavioral Control were significant positive predictors for intention to use VR. Future investigation should aim to test strategies to target these factors significantly influencing VR use to further address the gap between evidence and clinical practice in the use of VR for physical rehabilitation interventions.